Aging in psoriasis vulgaris: female patients are epigenetically older than healthy controls - Borsky, Pavel; Chmelarova, Marcela; Fiala, Zdenek; Hamakova, Kvetoslava; Palicka, Vladimir; Krejsek, Jan; Andrys, Ctirad; Kremlacek, Jan; Rehacek, Vit; Beranek, Martin; Malkova, Andrea; Svadlakova, Tereza; et al. (Immunity & ageing, 2021)
BACKGROUND: Psoriasis vulgaris is a skin autoimmune disease. Psoriatic patients have significantly lowered life expectancy and suffer from various comorbidities. The main goal of the study was to determine whether psoriatic patients experience accelerated aging. As accelerated aging might be the reason for the higher prevalence of comorbidities at lower chronological ages, we also wanted to investigate the relationship between aging and selected parameters of frequent psoriatic comorbidities - endocan, vascular endothelial growth factor and interleukin-17. Samples were obtained from 28 patients and 42 healthy controls. Epigenetic age measurement was based on the Horvath clock. The levels of endocan, vascular endothelial growth factor and interleukin-17 were analyzed using standardized ELISA methods. RESULTS: The difference between the epigenetic age and the chronological age of each individual subject did not increase with the increasing chronological age of patients. We cannot conclude that psoriasis causes accelerated aging. However, the epigenetic and chronological age difference was significantly higher in female patients than in female controls, and the difference was correlated with endocan (r = 0.867, p = 0.0012) and vascular endothelial growth factor (r = 0.633, p = 0.0365) only in female patients. CONCLUSIONS: The findings suggest a possible presence of pathophysiological processes that occur only in female psoriatic patients. These processes make psoriatic females biologically older and might lead to an increased risk of comorbidity occurrence. This study also supports the idea that autoimmune diseases cause accelerated aging, which should be further explored in the future.
Keywords: Comorbidities; Psoriasis; Epigenetic clock; Aging